The effect of full annealing on the microstructure and mechanical properties of cold draw low carbon steel (2013)
The aim of this work is to determine the mechanical properties of cald drawn low carbon steel subjected to full annealing. The specimens were slowly heated up to a temperature of 900 followed by soaking treatment of 60 minutes under this temperature in a muffle furnance. Tensile, charpy and brinnel hardness tests were conducted to determine the yield strengths, tensile strengths, impact strengths and hardness of the annealed steel. The yield strength, tensile strength, hardness and toughness of the nail are greater in the non-treated nails when compared to the fully annealed nails at 60 minutes soaking time. The microstructure analysis showed that rate of grain nucleation and recrystalization increased with increasing degree of cold-drawn deformation. Grain growth was observed at higher degree of deformation leading into reduction in the mechanical properties of the material. It is evident from the resulting mechanical properties of the nails and the microstructure analysis that desired properties of the nails could be obtained by controlling the microstructure evolution of the low carbon steel in annealing.